A Critical Review of the Fisheries Policy: Total Allowable Catches and Rations for Cod in the North Sea - Frank Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
A purpose of this paper is to give a critical review of the total allowable catch (TAC) policy within the European Union (the EU) for cod in the North Sea. The actual TACs are compared with the biological recommendations about the TAC and the bio-economic optimal TAC. It is shown that the actual TAC follows biological recommendations but that bio-economic principles are poorly reflected in the TAC. The Danish regulatory policy for cod in the North Sea (rations) is analysed by means of a bio-economic model. It is shown that the information requirements needed for conducting a bio-economic optimal allocation of rations are considerable. Furthermore, the actual allocation scheme for rations distribute too high a share of the EU determined Danish quota to small vessels. Taxes and individual transferable quotas (ITQs) combined with bio-economic optimal TACs is presented as an alternative to the existing policy.
Keywords: 330; Cod in the North Sea; Total Allowable Catches; Rations; Taxes and Individual Transferable Quotas; EU-Fischereipolitik; Nordsee